2014
DOI: 10.2355/tetsutohagane.100.359
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Hydrogen Embrittlement on Hot-Sheared Surface during Die-Quench Process

Abstract: This study investigated resistance of hydrogen embrittlement on a hot-sheared surface of die-quenched steel sheets. The specimens were sheared at 750 ºC and 650 ºC after austenitization, and then quenched by water cooling. Additionally, the specimens were cathodically hydrogenized for 48 hours to accelerate cracking by hydrogen embrittlement. This sequence resulted in the residual tensile stress of over 1 GPa on the sheared surface and hydrogen concentration of about 1.5 ppm. Despite these severe conditions, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The solubility of hydrogen in bcc ferrite is very low and the diffusion rate is very high (Loidl et al , 2011; Michler and Naumann, 2010; Solheim and Solberg, 2013). Therefore, the ability of ferrite to improve the HE resistance of the 17-4PH stainless steel can be related to its ability to absorb part of plastic deformation work and reduce the stress concentration caused by martensitic transformation (Matsuno et al , 2014; Yang et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of hydrogen in bcc ferrite is very low and the diffusion rate is very high (Loidl et al , 2011; Michler and Naumann, 2010; Solheim and Solberg, 2013). Therefore, the ability of ferrite to improve the HE resistance of the 17-4PH stainless steel can be related to its ability to absorb part of plastic deformation work and reduce the stress concentration caused by martensitic transformation (Matsuno et al , 2014; Yang et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al (2002) showed that acicular ferrite and ultrafine ferrite have good resistance to HE and good mechanical properties. Matsuno et al (2014) and Yang et al (2018) found that adding ferrite into high-strength steels can absorb part of the plastic deformation energy and reduce the stress concentration caused by martensitic transformation, thereby reducing the HE susceptibility. However, the microstructure refined by low-temperature annealing can trap more hydrogen atoms at the interface (Yang et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Matsuno et al used hot-stamped steel sheets to quantify the residual stress at the sheared edge using X-ray measurements to investigate the effect of cold and hot shearing on hydrogen embrittlement at the sheared edge 11) . In this study, the stress components in two directions were quantified: the thickness direction and the perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%